The Estimation of Genetic Parameters of Yardlong Bean Yield Components (Vigna unguiculata ssp. sesquipedalis) - Kanina Zara Dini; Taryono Taryono; Rahmi Sri Sayekti (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2019)
The estimation of yield component genetic parameters is an important step towards plant breeding activities. This research aims to obtain information about yield components that can be used to increase yield of yardlong bean and accessions of yardlong bean for direct use or breeding materials. The research was conducted at Agrotechnology Innovation centre of Universitas Gadjah Mada, located in Kalitirto, Berbah, Sleman, Yogyakarta. The research materials consist of 29 accessions and 5 high yielding varieties as controls arranged in completely randomized design. Each accession was observed morphologically including days to 75% of ﬂowering, days to ﬁrst harvest, pod length, pod diameter, number of pods per cluster, number of pods per plant, number of seeds per pod, weight of 100 seeds, seed length, the diameter of seed, potential yield pods per hectare. Observed data were analyzed with ANOVA followed by the estimation of genetic parameters and principal component analysis. The results showed that almost all traits had a high heritability value, except seed length which had a moderate heritability value. Accessions 113, 134, 135, dan 137 could be considered as the promising candidates based on the earliest days to ﬁrst harvest and highest potential yield.